Study of Prescription Screening for Administrative and Pharmaceutical Aspects at CS Farma Pharmacy in the Period June-December 2018 - Afrisusnawati Rauf; Annisa Ika Muhrijannah; Hurria Hurria (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2020)
Incomplete prescribing can be one of the causes of medication errors in patients. This incident can be avoided by screening prescriptions by pharmacists at pharmacies which include administrative and pharmaceutical studies. The purpose of this study was to determine the administrative and pharmaceutical prescription completeness in June-December 2018 at CS Farma Pharmacy. The research method was descriptive nonexperimental with retrospective data collection. Samples were collected by simple random sampling technique and obtained 385 pieces of recipes that have met the inclusion criteria. The result shows that the completeness of administrative prescriptions consisted of: patient name 99,22%, patient age 88,05%, sex 9,09%, body weight 0%, doctor's name 3,64%, doctor's SIP 0% , prescription date 97,92%, doctor's address 100%, doctor's telephone number 0,26% and doctor's initial 6,23%. Pharmaceutical aspects consisted of: dosage form 69,61%, dosage strength 57,66%, drug stability 100% and incompatibility 100%. It can be concluded that the prescription in CS Farma Pharmacy on June-December 2018 was not complete administratively and pharmaceutically yet, based on Permenkes No.73 In 2016.